Educate to preserve: university extension in environmental education and planetary health in basic education - Santos Júnior, Claudio José dos; Silva, Jackson Pinto (Revista Ensino de Geografia (Recife), 2020)
Objective: To report the experience of the Extension Project “Educating to preserve: taking Environmental Education to the communities of Maceió”. Methods: This is a descriptive study of the Experience Report type developed from experiences of an extension action linked to the Federal Institute of Alagoas Campus Maceió (IFAL). Results: The Extension Project proposed educational activities and the approach to basic concepts of sustainability and environmental education. Topics such as basic sanitation, recycling, selective collection and trafficking and animal rights were worked on. The project included 40 students between the 7th and 9th grade of elementary school at an elementary school in Maceió-AL. The knowledge was worked in the classroom, in a dynamic and interactive way, using active learning methodologies. The students were free to express their opinions in the classroom about the proposed themes and, at each conclusion of a new theme, they were encouraged to multiply the knowledge acquired and challenged to share their learning with their community (students from other classes, family, friends and neighbors). Final considerations: With the implementation of the project, the target audience contributed to the development of a critical and sustainable awareness about the “environment” theme. The experience made it possible to approach the disciplines of geography and science in an integrated way and associated with the students' daily lives.